The Assessment System in Teaching Arabic in the Modern Junior High School and the Traditional Religious School/ التحول نظام التقويم في تعليم اللغة العربية بالمدرسة المتوسطة الحكومية الحديثة والمدرسة الدينية التقليدية - Hasna Qonita Khansa (Universitas Negeri Malang, 2021)
This study aims to describe the authentic assessment process, the competence measured in the authentic evaluation process, and the use of test instruments for authentic assessment in learning Arabic at MTsN 1 Malang City and Madrasah Diniyyah Nurul Ulum 2 Malang. The research design used a qualitative method. The results of this study were (1) authentic assessment used was observation and portfolio, (2) competence measured in the authentic assessment process following language objectives, and (3) various test instruments used.